2020
DOI: 10.2147/ott.s249202
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Expression of hsa_circRNA_001387 in Nasopharyngeal Carcinoma and the Effect on Efficacy of Radiotherapy</p>

Abstract: Background: Nasopharyngeal carcinoma (NPC) is one of the most difficult cancers to be detected and treated. Hunting for novel cancer-specific biomarkers for NPC patients is helpful for timely diagnosis and clinical treatment of NPC. Methods: In this study, high-throughput circRNA sequencing was used to screen the circRNAs with expression variation in NPC patients. qRT-PCR was used to detect the expression level of hsa_circRNA_001387 in the cancer tissues from 100 surgical patients, the peripheral blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…The main treatment for NPC is radiotherapy ( 32 ). Intensity-modulated radiotherapy (IMRT) is the most prominently used technique for treating patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment for NPC is radiotherapy ( 32 ). Intensity-modulated radiotherapy (IMRT) is the most prominently used technique for treating patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Previous studies found that abnormal circRNA is associated with the chemoresistance or radioresistance of malignant tumors, for example, Liu et al reported that circ_EIF6 knockdown significantly decreased the cisplatin-resistance of thyroid cancer cells by decreasing cell autophagy via sponging miR-144-3p. 22 Recent studies have found that circRNAs (including circ_CCDC66, 23 circ_000543, 24 and circ_001387 25 ) are involved in cancer cell radiosensitization by inhibiting the malignant biological behavior of cancer cells. However, there is no direct evidence to support the association between circRNAs and the radioiodine resistance of DTC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a marked upregulation of hsa_circRNA_001387, which could be used as a novel NPC biomarker, has been reported. The ROC curve for the determination of the diagnostic value of hsa_circRNA_001387 showed a high accuracy, indicating that this circRNA could be a specific and sensitive NPC marker ( 87 ).…”
Section: Circrnas As Tools For the Diagnosis And Prognosis Of Viral Infection-related Diseasesmentioning
confidence: 99%